ARM SLAM SKILL TRAINING MODEL FOR BEGINNER WRESTLING ATHLETES - Prasaja, Mochamad Derry; Widiastuti; Samsudin (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This study aims to improve the throwing skills of wrestling athletes aged 13-15 years. The research was carried out in early June to late June 2024 at the POPB DKI Jakarta Wrestling Sports Hall. The study was attended by all wrestling athletes aged 13-15 years, consisting of 30 athletes. The method used in this study is Research & Development with the ADDIE method. The instrument used is the Arm Throw skill test for ages 13-15 years which has been validated by martial arts expert lecturers, wrestling lecturers and wrestling coaches. Based on the initial test data for arm throw skills, an average result of 95.8333 was obtained. Then after being given training material in the study to improve wrestling arm throw skills for ages 13-15 years for 8 meetings, a final test was carried out with an average result of 104.5333 There is an increase in wrestling arm throw skills for ages 13-15 years.